Saprahan: Mutual Cooperation Value in Local Wisdom of Seranggam Village of Sambas Regency, Indonesia - Rianawati, Rianawati (Opción, 2019)
Local wisdom is sacred and is carried out with rules that must be obeyed, if it violates or does not implement it, something bad will happen. However, adher- ence to the values of local wisdom is now only ignored and underestimated by the community, so the values that contained in each of the traditional cultural customs that were previously highly valued and strongly held by the commu- nity, are now only as parental stories of the past. One of the local wisdoms is the tradition of saprahan that has been carried out by the Sambas Malay com- munity hereditary continously since time immemorial. This research used an ethnographic approach with qualitative methods. Data collected by deep in- terview and participan of observation. Finding of this research shows that the tradition of saprahan is not only done only among the nuclear family, but the tradition of saprahan is also done among large extended families in various parties, tahlilan, and various other events. Many values are contained in the culture of saprahan. The saprahan is a local wisdom which is a means for the formation of social solidarity and mutual cooperation that serves to maintain the existence of a common life, maintain harmony in family and community life, and become the driving force of motivation to grow community life. But the reality nowadays, the tradition of saprahan began to erode. Families who have an interest are no longer bothered with party meal preparations. Be- sides that, it has entrenched the attitude of individualism among the people. Therefore, the values of mutual cooperation and social solidarity that is very bound and stand up hold in the tradition of saprahan automatically disappear in people’s lives. The erosion of the value of mutual cooperation, by itself the character of sympathy, empathy, and social care will also fade in people’s lives